Epidural Tunneling for Effective Management of Severe Cancer Pain: A Case Report - Imam Safi'i; Ristiawan Muji Laksono (Journal of Anesthesiology and Clinical Research, 2025)
Introduction: Severe pain is a common and debilitating symptom for many cancer patients, often requiring multimodal approaches for effective management. While oral opioids and adjunctive therapies are frequently the first line, some patients with refractory pain necessitate interventional procedures. This case report describes the successful use of epidural tunneling for long-term pain management in a patient with severe cancer pain due to bone metastases. Case presentation: A 55-year-old woman with severe cancer pain secondary to bone metastases from breast cancer presented with intractable pain in her hips, buttocks, and legs, radiating to her feet with associated numbness. Despite high doses of oral opioids, paracetamol, amitriptyline, and a fentanyl syringe, her pain remained poorly controlled, significantly impacting her sleep and quality of life. A lumbosacral X-ray revealed osteolytic-blastic lesions with vertebral compression and other metastatic involvement. Given the severity and refractory nature of her pain, an epidural tunneling procedure was performed. Conclusion: Epidural tunneling proved to be a safe and effective method for managing severe, chronic cancer pain in this patient, leading to a substantial reduction in pain intensity and a decreased need for systemic opioids. This technique offers a valuable option for patients with persistent pain who have failed conventional analgesic therapies, particularly in advanced stages of cancer.